Theoretical Screening of Single Transition Metal Atoms Embedded in MXene Defects as Superior Electrocatalyst of Nitrogen Reduction Reaction. Issue 11 (26th June 2019) - Li, Lei; Wang, Xingyong; Guo, Haoran; Yao, Ge; Yu, Haibo; Tian, Ziqi; Li, Baihai; Chen, Liang
Abstract: The MXene‐supported single transition metal systems have been reported as promising electrocatalysts for hydrogen evolution reaction (HER) and carbon dioxide reduction reaction. Herein, the potential performance of MXene‐based catalysts was explored on nitrogen reduction reaction (NRR). Density functional theory computations are carried out to screen a series of transition metal atoms confined in a vacancy of MXene nanosheet (Mo2 TiC2 O2 ). The results reveal that the Zr, Mo, Hf, Ta, W, Re, and Os supported on defective Mo2 TiC2 O2 layer can significantly promote the NRR process. Among them, Zr‐doped single atom catalyst (Mo2 TiC2 O2 ‐ZrSA ) possesses the lowest barrier (0.15 eV) of the potential‐determining step, as well as high selectivity over HER competition. To the best of knowledge, 0.15 eV is the lowest barrier of potential‐determining step that has been reported for NRR so far. Besides, the formation energy of Mo2 TiC2 O2 ‐ZrSA is much more negative than that of the synthesized Mo2 TiC2 O2 ‐PtSA catalyst, suggesting that the experimental preparation of Mo2 TiC2 O2 ‐ZrSA is feasible. This work thus predicts an efficient electrocatalyst for the reduction of N2 to NH3 at ambient conditions. Abstract : A series of MXene‐supported single transition metal systems are theoretically screened to explore the potential electrocatalysts for nitrogen reduction reaction. Among them, Zr‐doped single atom catalyst possesses the lowest barrier (0.15 eV) of the potential‐determining step, as well as high selectivity over hydrogen evolution. Furthermore, the simulations indicate that the designed material is stable, thus the experimental synthesis should be feasible.